2022
DOI: 10.3390/ijerph192417013
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Sarcopenia in Nursing Home Residents: A Cross-Sectional Study

Abstract: Objective: This study aimed to assess the nutritional status and sarcopenia in older people living in nursing homes. Methods: This cross-sectional study enrolled 386 older adults in nursing homes in Hunan Province, China. Assessments included the Mini Nutritional Assessment Short Form for nutrition risk, Dietary Diversity Score for dietary diversity and Mini Mental State Examination for cognitive status. Sociodemographic (e.g., age, sex and educational level), health-related characteristics (e.g., food intake,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In contrast, a study conducted by Hua et al found no significant relationship between MNA-SF and education level. However, consistent with our results, a Chinese study identified no association between marital and nutritional status among older adults [36]. Moreover, in our study, osteoporosis was significantly related to nutritional status, with a higher number of osteoporotic older adults categorized in the at risk of malnutrition or malnourished group than the wellnourished group.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In contrast, a study conducted by Hua et al found no significant relationship between MNA-SF and education level. However, consistent with our results, a Chinese study identified no association between marital and nutritional status among older adults [36]. Moreover, in our study, osteoporosis was significantly related to nutritional status, with a higher number of osteoporotic older adults categorized in the at risk of malnutrition or malnourished group than the wellnourished group.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies, including this study, found that nutritional status was significantly associated with skeletal muscle strength [42,43]. In contrast, a study conducted by Hua et al revealed no significant association between the MNA-SF and skeletal muscle strength measured using a digital hand dynamometer [36]. In addition, Hua's study [36] found a significant association between nutritional status and BMI and CC, while no significant association was found in the present study.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Malnutrition is a global problem among older adults in care facilities. Foreign studies have shown (Power et al., 2018) that the prevalence of malnutrition among older adults in nursing facilities ranges from 5% to 50%, while the presence or risk of malnutrition among older adults in nursing facilities in China ranges from 8.2% to 30% (Hua et al., 2022).…”
Section: Introductionmentioning
confidence: 99%